Perangkap Industri Budaya dalam Desain Lanskap di Pulau Bali - KOHDRATA, NANIEK (Jurnal Arsitektur Lansekap; Vol.3, No.1, April 2017DO - 10.24843/JAL.2017.v03.i01.p12, 2017)
ABSTRACT A Cultural Industry Trap on Landscape Design in Bali Island Landscape architecture is a field in applied science that characterized by its multi-discipline approaches. However, people mostly correlate landscape architecture as a field of science and profession to deal with design dan art, especially with gardens. This paper, will discusse the issue of landscape design in Bali from the perspective of cultural studies. Landscape design activities are include but not limited to material objects, such as parks, streetscapes, cityscapes, and other landscape design products. It seems that present landscape design tastes have started from the western world. One of the landscape architects who criticize landscape design is Marc Treib. He primarily criticized the landscape design discourse occurring in the United States. Treib three canons about landscape tastes have shown applicable to recent landscape design conditions in Bali Island. Especially because there are still many landscape architects from abroad have been working in Indonesia projects, as well as landscape architects graduates of America and other western countries. Bali is a heaven for those landscape architects to set their status of fame for it provides amount of opportunities in hotel and resort landscape design and private villas gardens as well. The influence of scholars and design values emerge in Bali, especially in the public and semi-public sectors is colored by Western design "ideologies". Keywords: landscape design, design taste, design discourse,western design ideology.